EDUKASI DAUR ULANG LIMBAH GONGGONG KEPADA KELOMPOK MASYARAKAT PESISIR KAMPUNG SEI JANG TANJUNGPINANG, KEPULAUAN RIAU - Febrianti Lestari; Rika Anggraini; Harapin Hafid (Universitas Halu Oleo, 2022)
Community service activities have been carried out regarding education on recycling bark waste for the Sei Jang Tanjungpinang coastal community group. The purpose of this activity is to provide knowledge to the community regarding the technical recycling of recycling bark waste shells into useful-value products. This is an effort to minimize large waste from leftover seafood which is inorganic and very difficult to decompose in the environment. The problem faced by the community is an increase in the amount of food waste originating from seafood, especially the Barking Snail (Strombus sp). Along with an increase in population and an increase in the number of culinary tourists visiting Tanjungpinang City, it will have an impact on increasing the volume of shell waste, which will ultimately have an impact on increasing the load of waste discharged into the aquatic environment. This is a very serious problem to be addressed, considering that the shell waste is very difficult to degrade in nature. The method used in this activity is practical training methods and assistance in the process of recycling bark waste shells to produce handicraft products in the form of handicrafts in the form of flower decorations and other handicrafts, as well as assistance to form community groups that recycle shells by flying. The results that have been achieved in this activity are the realization of the application of science and technology through the application of technical cleaning and bleaching and processing of Gonggong shell waste into environmentally friendly products. In addition, the formation of community institutions for coastal community groups that are able to manage and carry out joint activities in recycling waste into handicraft products in the form of handicrafts that can bring in income for the community.